Resiliensi Perawat Dalam Melakukan Pelayanan Keperawatan Di Masa Pandemi Covid-19 Di Rumah Sakit: Nurses Resilience in Performing Nursing Services During the Covid-19 Pandemic in Hospitals - Priningsih, Fitria (Dohara POAJ, 2022)
Introduction: Resilience is the ability to recover in a difficult condition, to return to normal after heavy stress. As is currently happening, Covid-19 is a world problem that we must face together, especially for nurses who are at the forefront of health services. Methods: This study used a descriptive qualitative approach, using 6 informants with a purposive sampling technique. A qualitative approach was carried out by in-depth interviews and observations of nurses working in Cocid-19 room to get an in-depth description of nurse resilience. Results: The results of this study illustrate the methods used by nurses to stay afloat. Resilient nurses have resilient individual psychological capital including emotional regulation, impulse control, empathy, optimism, causal analysis, self-efficiency, good reaching out, and resources. resilience includes I am, I can, I have in him. Discussion: From the results of this study the six informants have a high level of spirituality, an unyielding attitude, a feeling of patience, mutual respect, and have a lot of support from the closest people, the environment, and a love for the nursing profession.